The Development of human insulin precursor expressed from P.pastoris-X33 in a 10L-fermenter - Dian Japany Puspitasari (Indonesian Journal of Science and Education, 2023)
Human insulin is a hormone that regulate blood glucose in human. Due to the vital role of insulin and the trend of diabetic case globally, insulin demand has been rise in the world. Indonesia as a country that had diabetic patient more than 10 million people in 2017 is still imported raw material of human insulin. The development of production process of human insulin is needed in order to support government objective to be independence in medicine aspect. Human insulin precursor (HIP) expressed from a Pichia pastoris X33/pD902-IP had been developed and optimised in a small scale. However, the scaling up in fermenter 10L has not been studied. Using a 10L-fermenter the fermentation system of P.pastoris X33/pD902-IP was developed. Fermentation done in 120 hours using a basal salt medium (half concentration) for the vegetative and induction media. To induce HIP expression, methanol is fed by pulse strategy with a gradient concentration 1-3% for 48 hours. The dry cell weight (DCW) and HIP titer were 72 g/L and 192 mg/L, respectively. This development is the first fermentation process of HIP in fermenter 10L in Indonesia.